Integration of oral health-related quality of life instruments. (October 2016) - John, Mike T.; Reissmann, Daniel R.; Čelebić, Asja; Baba, Kazuyoshi; Kende, Dóra; Larsson, Pernilla; Rener-Sitar, Ksenija
Abstract: Objectives: To integrate items from two widely used oral health-related quality of life (OHRQoL) questionnaires, the General Oral Health Assessment Index (GOHAI) and the Oral Impacts on Daily Performances (OIDP), as well as culturally-specific items of the Oral Health Impact Profile (OHIP) into a four-dimensional OHRQoL model consisting of Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact . Methods: Subjects came from an ancillary study of the Dimensions of Oral Health-Related Quality of Life Project (N = 267 patients, mean age ± SD: 54.0 ± 17.2 years, 58% women.) Patients filled in the original 49 items of OHIP and 22 additional OHRQoL items in a cross-sectional study. These additional items consisted of 7 culturally specific OHIP items and 15 GOHAI or OIDP items with unique content not covered in OHIP-49. Before data collection, three experts hypothesized to which of the four OHRQoL dimensions these items belong. Hypotheses were tested in correlation analyses between the 22 items and the four dimension scores that were derived from OHIP-49. Results: Five of the 22 items did not provide sufficient information to which dimension they belong. In 16 of the remaining 17 items, the pattern of correlation coefficients fitted experts' a priori hypotheses. Acceptance of 16 of the 17 hypotheses was interpreted as evidence that additional (not in OHIP-49 contained) OHRQoL items can be assigned to Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact . Conclusion: Items of three OHRQoL instruments can be integrated into a dimensional OHRQoL model consisting of Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact . Clinical significance: Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact can serve as a simple and clinically appealing set of oral health-related quality of life (OHRQoL) dimensions and therefore provide an opportunity for simpler, but psychometrically improved OHRQoL measurement in the future.